APPLICATION OF BIOURINE ON GROWTH AND YIELD OF SHALLOT FERTILIZED WITH INORGANIC AND ORGANIC FERTILIZER IN BATU, EAST JAVA - Mudji Santosa; Agus Suryanto; Moch. Dawam Maghfoer (AGRIVITA, Journal of Agricultural Science, 2015)
The experiment was done in order to know the influence of Biourine on growth and yield of shallot fertilized with organic and inorganic fertilizers in Batu, East Java, 900 m asl, 24-27 0C, Andosol soil, from May to July 2014. A Factorial Randomized Block Design was used in arranging treatments i.e. applied of Biourine (with and without Biourine) and applied of organic-inorganic fertilizer. The results showed that the application of Biourine and inorganic fertilizer increased growth and yield of shallot var. Philippines. Shallot var. Philliphines applicated with Biourine 1000 L ha-1 and 100 kg N ha-1 (ZA); 50 kg P2O5 ha-1 (SP36) and 70 kg K2O ha-1 (KCl) showed the highest bulb yield (1,932.2 kg m-2) and  the lowest showed the treatment of 5 t ha-1 organic fertilizer without Biourine with yield of 1,285.7 kg m-2 or increased 50.3%.